Gizzard vs. teeth, it's a tie: food-processing efficiency in herbivorous birds and mammals and implications for dinosaur feeding strategies. Issue 4 (8th April 2011) - Fritz, Julia; Hummel, Jürgen; Kienzle, Ellen; Wings, Oliver; Streich, W. Jürgen; Clauss, Marcus
Abstract : Particle size reduction is a primary means of improving efficiency in herbivores. The mode of food particle size reduction is one of the main differences between herbivorous birds (gizzard) and mammals (teeth). For a quantitative comparison of the efficiency of food comminution, we investigated mean fecal particle sizes (MPS) in 14 herbivorous bird species and compared these with a data set of 111 non-ruminant herbivorous mammal species. In general MPS increased with body mass, but there was no significant difference between birds and mammals, suggesting a comparable efficiency of food processing by gizzards and chewing teeth. The results lead to the intriguing question of why gizzard systems have evolved comparatively rarely among amniote herbivores. Advantages linked to one of the two food comminution systems must, however, be sought in different effects other than size reduction itself. In paleoecological scenarios, the evolution of "dental batteries, " for example in ornithopod dinosaurs, should be considered an advantage compared to absence of mastication, but not compared to gizzard-based herbivory.